Comparison of Experimental and Modeled EMI Shielding Properties of Periodic Porous xGNP/PLA Composites - Avi Bregman (Polymers, 2019)
Microwave absorbing materials, particularly ones that can achieve high electromagnetic interference (EMI) absorption while minimizing weight and thickness are in high demand for many applications. Herein we present an approach that relies on the introduction of periodically placed air-filled pores into polymer composites in order to reduce material requirements and maximize microwave absorption. In this study, graphene nano platelet (xGNP)/poly-lactic acid (PLA) composites with different aspect ratio fillers were characterized and their complex electromagnetic properties were extracted. Using these materials, we fabricated non-perfect electrical conductor (PEC) backed, porous composites and explored the effect of filler aspect ratio and pore geometry on EMI shielding properties. Furthermore, we developed and experimentally verified a computational model that allows for rigorous, high-throughput optimization of absorbers with periodic porous geometries. Finally, we extend the modeling approach to explore the effect of pore addition on PEC-backed composites. Our composite structures demonstrated decreased fractions of reflected power and increased fractions of absorbed power over the majority of the X Band due to the addition of periodically arranged cylindrical pores. Furthermore, we showed that for xGNP/PLA composite material, reflection loss can be increased by as much as 13 dB through the addition of spherical pores. The ability to adjust shielding properties through the fabrication of polymer composites with periodically arranged pores opens new strategies for the modeling and development of new microwave absorption materials.